Nanoscience and nanotechnology :Fundamentals to Frontires - Rao, M.S. Ramachandra; Sing,Shubra (India Wiley India Private Limited, 2013)
This book explains scientific foundations governing the functionality of nanostructures and makes the reader familiar with several basic and applications aspects of nano-structured systems.
Keywords: nanotechnology